Pengaruh Pola Asuh Orang Tua dan Motivasi Belajar Terhadap Prestasi Belajar Siswa pada Mata Pelajaran Pendidikan Kewarganegaraan Kelas XI SMA Negeri 5 Pematangsiantar Tahun Ajaran 2025/2026: Penelitian - Dion Adinar Fortino Siallagan; Sanggam M. Siahaan; Prini Desima Evawani (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to determine the influence of Parenting Patterns and Learning Motivation on Student Learning Achievement in Civics Subjects of Class XI SMA Negeri 5 Pematangsiantar in the 2025/2026 Academic Year. The population in this study were all 355 class XI students and the sample in this study was 35 class XI-2 students and 36 class XI-8 students. So the sample used was 71 class XI-2 students and XI-8 students. The instruments used were questionnaires and documentation. The quality of the research instruments for questionnaires and student learning achievement was assessed through documentation of student achievement results from the school. All data from the three variables above were first tested for normal distribution using a goodness-of-fit test or Chi-square test. The results of the simple linear regression analysis yielded the following values: R = 0.693, indicating a strong positive relationship between Parenting Style (X1) and student achievement (Y). This means that the higher the Parenting Style (X1), the better the student's academic achievement. R2 = 0.759, indicating that 75.9% of the variation in academic achievement can be explained by Learning Motivation (X2). The remaining 24.1% is influenced by other factors not included in the regression model.